Association of glucagon-like peptide-1 receptor agonists with atrial fibrillation recurrence after catheter ablation: a systematic review and meta-analysis - Dan He; Defu Lv; Jiaxin Tang; Xiaojuan Liao; Ping Mao; Zhu Tian (Frontiers in Cardiovascular Medicine, 2026)
Background Current studies suggest a potential association between the use of glucagon-like peptide-1 receptor agonists (GLP-1RAs) and atrial fibrillation (AF) recurrence after catheter ablation, but the findings remain controversial. Therefore, we conducted a meta-analysis to evaluate this association, aiming to provide evidence for clinical prevention and treatment. Methods We systematically searched PubMed, Embase, Web of Science, Cochrane Library, and four Chinese databases (CNKI, WanFang, VIP, and CBM) up to June 10, 2026, for studies on the association between GLP-1RAs and AF recurrence following catheter ablation. Two researchers independently screened literature, extracted data and assessed study quality. Statistical analyses were performed using Review Manager 5.3 and R 4.6.0. Results A total of seven studies involving 7,907 patients were included. The meta-analysis showed that the use of GLP-1RAs was associated with a reduced risk of AF recurrence after catheter ablation (HR = 0.52, 95%CI = 0.37–0.73, P < 0.001). Subgroup analyses consistently demonstrated a protective effect of GLP-1RAs on AF recurrence, irrespective of sample size (≤200: HR = 0.34, 95%CI = 0.22–0.52, P < 0.001 vs. > 200: HR = 0.70, 95%CI = 0.53–0.91, P = 0.009), study design (prospective: HR = 0.56, 95%CI = 0.43–0.72, P < 0.001 vs. retrospective: HR = 0.47, 95%CI = 0.25–0.89, P = 0.020), or follow-up duration (≤12 months: HR = 0.53, 95%CI = 0.40–0.72, P < 0.001 vs. > 12 months: HR = 0.58, 95%CI = 0.35–0.95, P = 0.030). Conclusions The use of GLP-1RAs may reduce the risk of AF recurrence after catheter ablation. However, the 95% prediction interval crossed the null value, indicating that this protective effect is not definitive. Given the limitations of this study, further high-quality randomized controlled trials are warranted to confirm these findings.